Genres, sexualités et médias : enjeux politiques, identitaires et disciplinaires dans l’université francophone - Marie-Hélène/Sam Bourcier; Élisabeth Mercier (Communiquer)
Marie-Hélène/Sam Bourcier made a considerable contribution to queer studies in France and elsewhere in the francophonie. Nevertheless, this field of study remains strongly associated with Anglo-Saxon traditions of research, as well as to cultural studies and other critical approaches linked to minority issues (postcolonial, trans, black, etc.). This interview, conducted at the 7e Congrès international des recherches féministes dans la francophonie, first expands on the work, and its reception, of Marie-Hélène/Sam Bourcier as a researcher and activist. Also, it discusses the political contributions of critical studies directed on gender and sexuality within the francophone university.